Symposia Training, 24 Jun 2010 - Universiti Malaysia Sarawak, Centre for Academic Information Services (Centre for Academic Information Services, 2010)
Training Symposia ini diadakan pada 24 Jun 2010 di Makmal Komputer tingkat 1 PKMA.